THE INFLUENCE OF DEBATE TECHNIQUE, AND STUDENTS' CRITICAL THINKING TOWARDS THEIR SPEAKING ABILITY - Djena Ali; Threesje Roza Souisa (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2019)
This study is aimed at a) describing the students speaking ability and their critical thinking level, b) finding out the significant influence of speaking ability between the students who are taught with debate technique and those who are taught with group discussion technique, c) finding out the significant differences in speaking ability between the students who have high critical thinking and those who have low critical thinking, and d) finding out the significant interaction in speaking ability between teaching techniques and critical thinking skill.The quasi-experiment method under a quantitative approach was used to conduct the study. The design of the study is 2x2 with pre-post-test control group design. In analyzing the data, descriptive and inferential statistics were used. The results show that the students‟ speaking ability is in the high level, whereas in critical thinking skill there were 48 students who can be categorized as having high critical thinking and 32 students who have low critical thinking. The students who are taught by using debate technique have better achievement in speaking ability than those who are taught with discussion technique. There is a positive and significant influence on students speaking ability between the students who are taught by debate technique with those who are taught with discussion technique. There is a positive and significant difference in speaking ability between the students who have high critical thinking and those who have low critical thinking. There is a positive and significant interaction of speaking ability between the teaching techniques and critical thinking.